2022
DOI: 10.3389/fmed.2021.759559
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Encephalitis With Multiple Auto-Antibodies With Concomitant Human Herpesvirus-7 and Ovarian Teratoma: A Case Report

Abstract: Infectious etiologies and tumors are common triggers of autoimmune encephalitis. We herein reported a rare case of autoimmune encephalitis with multiple autoantibodies in cerebrospinal fluid (CSF) and serum, with concomitant human herpesvirus 7 (HHV-7) infection and ovarian teratoma. A 36-year-old woman presented with mental and behavioral changes and gibberish for 13 days, followed by fever for 1 day. Her brain MRI indicated limbic encephalitis. Metagenomic next-generation sequencing (mNGS) of CSF revealed HH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…anti-Hu, Yo, and Ri antibodies) ; (2) antibodies acting on neuronal cell-surface receptors or synaptic proteins (e.g. anti-NMDAR, mGluR5, GABABR, LGI1, and AMPAP antibodies), some of which can occasionally overlap with each other, such as the combination of anti-NMDAR antibodies with anti-GABABR antibodies, anti-NMDAR antibodies with anti-IGI1 antibodies, and anti-NMDAR antibodies with anti-AMPAP antibodies ( 12 , 27 , 28 ). Of note, it is unclear why both antibodies are present in our patient, given their uncommon coexistence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…anti-Hu, Yo, and Ri antibodies) ; (2) antibodies acting on neuronal cell-surface receptors or synaptic proteins (e.g. anti-NMDAR, mGluR5, GABABR, LGI1, and AMPAP antibodies), some of which can occasionally overlap with each other, such as the combination of anti-NMDAR antibodies with anti-GABABR antibodies, anti-NMDAR antibodies with anti-IGI1 antibodies, and anti-NMDAR antibodies with anti-AMPAP antibodies ( 12 , 27 , 28 ). Of note, it is unclear why both antibodies are present in our patient, given their uncommon coexistence.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, co-existing antibodies may produce an overlap of clinical symptoms in patients with AE, increasing the probability of potential malignancy (11). Literature reports indicate that anti-NMDAR encephalitis occurs mostly in women with an average onset age of approximately 21 years and is frequently related to tumors, especially ovarian teratomas (12)(13)(14). A recent systematic review of anti-NMDAR encephalitis found that the most common brain magnetic resonance imaging (MRI) outcome was abnormal temporal lobe signals in the medial temporal lobe with hyperintensity on fluid-attenuated inversion recovery (FLAIR), followed by cortical gray matter changes and subcortical white matter changes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, our case, despite an extensive viral screening and thorough malignancy evaluation, showed negative results for viral agents and no evidence of cancer. This juxtaposition highlights the diverse etiologies within AE and underscores the importance of individualized diagnostic approaches [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [13] reported that a child developed AE with the co-existence of GABA B R and NMDAR antibodies after the herpes simplex virus encephalitis. Yang et al [14] reported a AE patient with NMDAR and AMPAR antibodies followed by human herpesvirus 7 (HHV-7) infection and ovarian teratoma. Autoimmune response secondary to the release of antigens from damaged brain tissue after viral infection might be responsible for the multiple auto-antibodies production.…”
Section: Discussionmentioning
confidence: 99%